Analisis Kinerja Keuangan Menggunakan Rasio Likuiditas, Rasio Solvabilitas dan Rasio Profitabilitas pada PT Mayora Indah Tbk Untuk Periode Tahun 2022-2024 - Sintia Sintia; Nadine Allifia; Mufidah Syahrani; Angga Sanita Putra (Jurnal Riset Rumpun Ilmu Ekonomi, 2025)
This study aims to assess the financial performance of PT Mayora Indah Tbk from 2022 to 2024 using several financial ratios, including liquidity, solvency, and profitability. The method used in this study is a quantitative approach. In this study, the data analyzed is secondary data, where the population includes all financial statements of PT Mayora Indah Tbk. The sample taken for this study is the financial statements of PT Mayora Indah Tbk in 2022-2024. The results of the analysis show that the company's liquidity ratio is in good condition with Current Ratio (CR) reaching 298.3% and Quick Ratio (QR) of 216.8%, which exceeds existing industry standards. On the solvency ratio, the Debt To Asset Ratio (DAR) was recorded at 40.3%, which is significantly higher than the industry standard of 35%, indicating a situation that is not ideal. Conversely, the Debt To Equity Ratio (DER) of 67.9% shows a positive performance, which is below the industry standard of 90%. For profitability ratios, the company recorded a Net Profit Margin (NPM) of 8.4%, Return On Assets (ROA) of 10.9%, and Return On Equity (ROE) of 18.2%, all of which are below industry standards, indicating that profitability conditions are still low